PENGGUNAAN MEDIA VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM KELAS VI DI MADRASAH IBTIDAIYAH SWASTA AL-ISLAM PARIT JAWAI - Topik Topik (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This research uses a qualitative approach with descriptive research type. Data collection techniques using interviews, observation and documentation. The data analysis techniques used are data reduction, data display, conclusion and verification. The results showed that; 1) Visual media used to improve student learning outcomes in science subjects in class VI Year 2019-2020 lessons use image media. 2) The steps for implementing visual media to improve student learning outcomes in science subjects in class VI Academic Year 2019-2020 consist of several steps, namely: a) preparation by preparing media related to the material learning; b) implementation by paying attention to the media's relation to the material and students' conditions so that its use is correct; c) evaluate visual media by observing the media during the learning process and assessments after learning is complete. 3) The supporting factors for the use of visual media are internal factors that are present from the teacher's intention to foster student learning desire and to improve student learning outcomes, while the inhibiting factors for the use of visual media are less proficient in applying visual media and the lack of facilities and infrastructure makes teachers rarely use the media. visual. The use of visual media during learning can improve student learning outcomes which is depicted from student scores after a test at the end of learning.